Regulation and activity of CaTrk1, CaAcu1 and CaHak1, the three plasma membrane potassium transporters in Candida albicans - Ruiz-Castilla, Francisco J; Bieber, Jan; Caro, Gabriel; Michán, Carmen; Sychrova, Hana; Ramos, José (Biochimica et biophysica acta. Biomembranes, 2021)
Wild-type cells of Candida albicans, the most common human fungal pathogen, are able to grow at very low micromolar concentrations of potassium in the external milieu. One of the reasons behind that behaviour is the existence of three different types of K+ transporters in their plasma membrane: Trk1, Acu1 and Hak1. This work shows that the transporters are very differently regulated at the transcriptional level upon exposure to saline stress, pH alterations or K+ starvation. We propose that different transporters take the lead in the diverse environmental conditions, Trk1 being the "house-keeping" one, and Acu1/Hak1 dominating upon K+ limiting conditions. Heterologous expression of the genes coding for the three transporters in a Saccharomyces cerevisiae strain lacking its endogenous potassium transporters showed that all of them mediated cation transport but with very different efficiencies. Moreover, expression of the transporters in S. cerevisiae also affected other physiological characteristics such as sodium and lithium tolerance, membrane potential or intracellular pH, being, in general, CaTrk1 the most effective in keeping these parameters close to the usual wild-type physiological levels.
Keywords: Saccharomyces cerevisiae; Candida albicans; Hak1; Potassium transport; Acu1; Potassium; Cell Membrane; Fungal Proteins; Trk1; lidé; Cation Transport Proteins; draslík; fungální proteiny; Humans; Heterologous expression; proteiny přenášející kationty; buněčná membrána